National Cancer Control Programmes in Thailand - Srivatanakul, Petcharin (Indonesian Journal of Cancer, 2008)
National Cancer Control Programmes in ThailandÂ full text: http://www.scribd.com/doc/45152475/National-Cancer-Control-Programmes-in-Thailand